Eating Out: Fast Food Consumption and its Impact on Health of Young Generation of Karachi - Shaista Kamal Khan; Khurram Khan Alwi; Nimra Nadeem (Institute of Business Management, 2021)
This paper has measured the impacts of fast food on the health of the young generation. In today's age where both the genders are working as bread earners of the family, people prefer fast foods because of the convenience factor and eating fast food is affecting and influencing the health of the young generation. The core population, who consume fast food the most frequently is teenage youth. The study is based on value expectancy theory and attempts to develop and test a theory-based questionnaire that identifies factor relating to fast food consumption and impact on health. In this qualitative study, data is collected by interviews with seven persons. The predetermine open-ended questions had been made to investigate the thoughts of respondents and indicate the key meanings that each participant had described his or her experiences. After conducting interviews from participants then identified relevant themes and are further discussed in the results. All findings are supported by the literature review that is related to this study. Moreover, the qualitative study ends with some recommendations to the young generation.